Interpersonal Communication: Everyday Encounters, 9th Edition - Julia T. Wood (Cengage Learning, 2019)
INTERPERSONAL COMMUNICATION: EVERYDAY ENCOUNTERS, 9th Edition, relates theory and skills directly to students' everyday interactions as it delivers a solid introduction to interpersonal communication. An emphasis on cultural diversity is thoroughly woven throughout the new 9th edition, empowering you with the skills you need to effectively communicate with people who may not share a similar background. The new edition also features increased coverage of social media, including a section in every chapter that discusses connections between chapter themes and social media. The MindTap Mobile App, fully integrated with the text, lets you learn when and wherever you want. Read or listen to the text and study with the aid of instructor notifications, flashcards and practice quizzes.